Online control method for tobacco processing process parameters by using computer programs - LIU HUA; MA LINGLING; SHEN DEWU (2011)
The invention discloses an online control method for tobacco processing process parameters by using computer programs, which comprises the following steps of: acquiring temperature and humidity parameter values of a processed material, namely tobacco leaves or tobacco shreds through a temperature sensor and a moisture meter, acquiring running parameters of the real-time online acquisition processing process and the temperature or the humidity of the tobacco leaves or the tobacco shreds, comparing the running parameters of the real-time online acquisition processing process equipment and the temperature and humidity parameter values of the tobacco leaves or the tobacco shreds with the acquired parameter values of the temperature or the humidity of the tobacco leaves or the tobacco shreds before processing, transmitting modification instructions of control parameter setting provided by a data monitoring system to a programmable logic controller (PLC), and timely adjusting online control parameters and output in